Nurse practitioner scope of practice and the prevention of foot complications in rural diabetes patients. Issue 4 (8th June 2021) - Hughes, Danny R.; Filar, Candice; Mitchell, David T.
Abstract: Purpose: Diabetic foot ulcers afflict a quarter of type‐2 diabetes mellitus patients and are associated with higher mortality rates among people with diabetes. Routine primary and preventive care is essential to both prevent and treat foot ulcers before they can contribute to further adverse outcomes. One approach for expanding this care to people with diabetes in rural communities is increasing the practice authority of nurse practitioners. This study examines whether the presence of nurse practitioner practice authority is associated with fewer foot ulcer complications in rural populations as measured through the incidence of foot debridement—a common procedure for addressing severe diabetic foot ulcers. Methods: This study uses medical claims to estimate the incidence of foot debridement for US counties. A multivariable linear regression was performed to examine the association between nurse practitioner practice authority and the county incidence of foot debridement after adjusting for measures of local health care workforce and sociodemographics. Findings: Nurse practitioner practice authority was associated with 219.4 fewer foot debridements per 10, 000 enrollees ( P < .001) in rural counties. Rural health clinics ( P < .03) and skilled nursing facilities ( P < .03) were also associated with fewer rural debridements. The number of nurse practitioners ( P < .69) and primary care physicians ( P < .69) per enrollee were not significant. No measure of health care workforce was associated with the incidence of foot debridement in urban counties. Conclusions: Expanding nurse practitioner practice authority may be an effective solution for preventing complications from diabetic foot ulcers in rural communities.